Correlation Between Personality, Locus of Control, and Knowledge About Stunting with Mother's Responsibility Behavior Considering Toddlers at Posyandu - El Jannah, Syarifah Miftahul; Marbun, Rosmida M; Widyastuti, Arni (Poltekkes Kemenkes Palu, 2023)
Stunting is a failure to thrive due to chronic malnutrition, psycho-social stimulation, and exposure to repeated infections, especially in the first 1,000 days of life. Can be eliminated if growth from newborn to toddler is always monitored. Data from the Kebayoran Baru District Health Center as of December 31, 2018, there were 19% of infants did not weigh themselves regularly. The low participation of mothers in weighing their toddlers regularly every month at Posyandu is a problem in itself. It is necessary to examine and examine further personality, Locus of control, and mother's knowledge which will influence the behavior of the mother's responsibility to regularly weigh her child every month. This research is analytically descriptive with a total of 360 mothers who have toddlers in the working area of the Kebayoran Baru Health Center, data were collected using a questionnaire with the big five personality variables, Locus of control, and knowledge about stunting, data were processed using The analysis was performed with a statistical test using correlation test Pearson's. The results showed that education level 60% graduated from high school, 54.4% were aged 25-34 years, and 52.2% had high knowledge about stunting. The biggest personality type (187 people) is agreeableness, 83% have an Internal Locus of Control. There is a correlation between neuroticism personality type and responsible behavior for weighing toddlers (p=0.005) but there is no correlation between Locus of Control (p=0.067) and level of knowledge with responsible behavior for weighing toddlers (p=0.088).